2017
DOI: 10.4468/2017.3.04cesarani.nechita
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and the Sharing Economy. An Evidence from Airbnb Usage in Italy and Romania

Abstract: Tourism in the era of the sharing economy adopts a model based on a global concept with a local practice. The traditional tourism offer is based on the attractiveness of a destination, expressed by a system of characteristics of the destination itself and a range of services related to accommodation, transport and food. The tourism model of sharing economy, instead, is based on the development of shared services that stimulate the flows of tourists. Traditional destinations are then alongside new destinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Lastly, from a spatial perspective, previous studies have analysed the location of Airbnb listings at different scales (national, city or infra-municipal levels) and its relationship with other elements, such as tourism resources, socio-demographic profile of the resident population, housing market, cultural aspects and hotel offerings. Some researchers have studied the spread of Airbnb at the national level (Abdar and Yen, 2017;Cesarani and Nechita, 2017;Strommen-Bakhtiar and Vinogradov, 2019), while others have focused on the municipal or city level (Adamiak, 2018). In their study of eight US cities, Quattrone et al (2018) found that Airbnb listings tend to be clustered in central neighbourhoods and in areas occupied by creative classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lastly, from a spatial perspective, previous studies have analysed the location of Airbnb listings at different scales (national, city or infra-municipal levels) and its relationship with other elements, such as tourism resources, socio-demographic profile of the resident population, housing market, cultural aspects and hotel offerings. Some researchers have studied the spread of Airbnb at the national level (Abdar and Yen, 2017;Cesarani and Nechita, 2017;Strommen-Bakhtiar and Vinogradov, 2019), while others have focused on the municipal or city level (Adamiak, 2018). In their study of eight US cities, Quattrone et al (2018) found that Airbnb listings tend to be clustered in central neighbourhoods and in areas occupied by creative classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In building up the distributed trust in sharing economy, trusting strangers is essential (Ert et al , 2016; Etzioni, 2019; Ufford, 2015). Despite the high level of anonymity on the internet, according to Etzioni (2019), it is still possible to build trust, with the adoption of cyber trust mechanisms created between the members of the shared network (Cesarani and Nechita, 2017). Rating systems become an essential mechanism of sharing economy in identifying strangers’ trustworthiness, through rating and reviewing buyers and sellers after transactions (Pettersen, 2017; Utz et al , 2009).…”
Section: The Role Of Social Capital In Sharing Economymentioning
confidence: 99%
“…Gentrification may bring discord between resident owners and non-resident owners and their lessees in condominium-type accommodation (Sklar and Edwards, 2017). Cesarani and Nechita (2017) suggest that such negative neighbourhood impacts necessitate new land-use planning responses. Gant (2016), nonetheless, notes, "the pressure of vacation rental flats was already a fact [in typical hot spots] before the creation of Airbnb" (p. 3).…”
Section: Economic Viabilitymentioning
confidence: 99%
“…For example, nearly a third of greater Sydney's listings on Airbnb are held by individuals with multiple properties (Gurran and Phibbs, 2017), making them defacto hoteliers. Cesarani and Nechita (2017) lament that the Romanian laws are not clear about ways to regulate and tax Airbnb while in Barcelona the municipality stopped granting licences for tourist dwellings in 2014 in the face of rising black market subletting to tourists of rented dwellings (Llop, 2017).…”
Section: Economic Viabilitymentioning
confidence: 99%